Structure of Myocardium of Young Hypertensive Rats after Injection of Cryopreserved Human Cord Blood Nucleated Cells - Babijchuk, Lyudmila V.; Koval, Sergey N.; Babijchuk, Georgiy A. (Problems of Cryobiology and Cryomedicine, 2016)
Nowadays cell therapy is considered as a promising new method to treat various diseases of cardiovascular system. Experimental model of stress-induced arterial hypertension (AH) was used to study the histological features of heart tissues and blood vessels: we have performed histochemical and polarization-optical assessment of collagen and elastic fibers of myocardium of young rats before and after introduction of human cryopreserved cord blood nucleated cells (cCBNCs). It has been found that myocardium structure of young rats to day 30 after the hypertension onset had pathological changes. We have found the changes in muscle fibers, spasm of blood vessels, paresis of the veins and capillaries, perivascular edema and cardiosclerosis. To day 3 after application of cCBNCs the number and area of cardiomyocyte nuclei increased. These compensatory changes were accompanied with a pronounced neoangiogenesis. One month later the administration of cCBNCs the density of fibroblasts in cardiac muscle of hypertensive rats increased (number of fibroblasts per area unit) in interstitial connective tissue and around the blood vessels; no areas with signs of focal ischemia and cardiosclerosis were noted. Perivascular and interstitial edemas were less pronounced. Probl Cryobiol Cryomed 2016; 26(3): 271–287